URGENCY OF ARBITRATION CLAUSE IN DETERMINING THE RESOLUTION OF SHARIA ECONOMIC DISPUTES - Nita Triana (AHKAM : Jurnal Ilmu Syariah, 2018)
This study explains the importance of the arbitration clause in determining the resolution of sharia economic disputes. The settlement of economic disputes in the Court is less in the interest of the economic actors, because of the long time, the limited resources and the results of the win-loss cause damage to future business relations. Resolution of arbitration disputes is an alternative choice. The research method used is a qualitative method, a type of doctrinal research with a normative juridical approach. Dispute resolution arbitrarily has many advantages over litigation (Court), the nature of which prioritizes negotiations, can avoid hostility so that business relationships will still be intertwined properly. To ensure that in the future will use the arbitration event, if there is a dispute in a commercial agreement between the two parties it is important to make an arbitration clause separate from the commercial agreement (principal agreement). The arbitration clause is binding on both parties. The power of the arbitration clause will give legal consequences to prevent one of the parties who have agreed on an arbitration agreement to seek a dispute resolution in the Court. These legal consequences are usually implemented in the form of the right to file exceptions to absolute authority over a lawsuit or case filed with the Court whose parties have been bound by an arbitration agreement. Arbitration agreements (arbitration clauses) are very important to be carried out to smooth the movement of the sharia economy in the future, especially when the sharia economic movement is international. Arbitration in Islamic law has long been known as a form of dispute resolution known as tahkim. Tahkim is to appoint someone as a referee or peacemaker, by two or more people who are in dispute in order to settle the case which they have peacefully divided. The selected referee or peacemaker is a person who is approved by both parties because they are considered able to resolve the dispute between them. This person who acts as a referee, peacemaker or arbitrator in Islamic law is called hakam